2018
DOI: 10.1155/2018/3712067
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Support Surfaces on the Incidence of Pressure Injuries in Critically Ill Patients: A Randomized Clinical Trial

Abstract: Purpose To analyze whether a viscoelastic mattress support surface can reduce the incidence of stage 2 pressure injuries compared to a standard hospital mattress with pyramidal overlay in critically ill patients. Method A randomized clinical trial with intention-to-treat analysis was carried out recruiting patients with Braden scale ≤14 on intensive care unit admission from April 2016 to April 2017. Patients were allocated into two groups: intervention group (viscoelastic mattress) and control group (standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…With only a few ripple mattresses available in the health facilities, more equipment and pressure reducing devices need to be purchased to support patient care. The findings compare with a randomized clinical trial conducted in Brazil, which found reduced incidences of Pressure ulcers among moderate or higher risk critically ill patients who used viscoelastic support surfaces (Bueno de Camargo et al, 2018). This also agrees with the findings of a study conducted in Ethiopia on the prevalence and risk factors associated with Pressure ulcers which reported pressure-relieving devices as significant in reducing the prevalence of Pressure ulcers (Bereded, Salih & Abebe, 2018).…”
Section: Institutional Factors Affecting Management Of Pressure Ulcers Among Nursessupporting
confidence: 88%
“…With only a few ripple mattresses available in the health facilities, more equipment and pressure reducing devices need to be purchased to support patient care. The findings compare with a randomized clinical trial conducted in Brazil, which found reduced incidences of Pressure ulcers among moderate or higher risk critically ill patients who used viscoelastic support surfaces (Bueno de Camargo et al, 2018). This also agrees with the findings of a study conducted in Ethiopia on the prevalence and risk factors associated with Pressure ulcers which reported pressure-relieving devices as significant in reducing the prevalence of Pressure ulcers (Bereded, Salih & Abebe, 2018).…”
Section: Institutional Factors Affecting Management Of Pressure Ulcers Among Nursessupporting
confidence: 88%
“…The result showed that there was a significant difference in pressure injury prevention (p=0.44). This was in line with a study by de Camargo et al (2018) which found that pressure injury incidence with support surface was about 32.2% compared to the group with no support surface 80.6% (p≤0.001); viscoelastic could redistribute pressure and affect micro climate that could reduce skin moisture to prevent pressure injuries. Studies showed that the use of pressure air mattress and pillow to position patients successfully reduced pressure injuries, statistically significant about 4.1-17% (Lupe et al, 2015;Uzun et al, 2015).…”
Section: Support Surface (5 Th Strategy)supporting
confidence: 91%
“…A similar randomized clinical trial conducted by Bueno de Camargo et al [18], aiming to analyze whether a viscoelastic mattress support (intervention group) surface can reduce the incidence of stage II PUs compared with a standard hospital mattress (control group) with pyramidal overlay in critically ill patients, found that the frequency of PU was higher in the control group compared with the intervention group.…”
Section: Discussionmentioning
confidence: 99%